2008
DOI: 10.1007/s10964-008-9273-z
|View full text |Cite
|
Sign up to set email alerts
|

Parental Smoking-specific Communication, Adolescents’ Smoking Behavior and Friendship Selection

Abstract: In this study, we investigated whether parental smoking-specific communication is related to adolescents' friendship-selection processes. Furthermore, we investigated whether adolescents and their best friends influence each other over time, and what role parents play in this process. In the present study we used data from the Family and Health project in which at baseline 428 full families participated. In this 2-year, three-wave longitudinal study data were available from fathers, mothers, early adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
2
12
1
Order By: Relevance
“…These interactions are premised upon studies demonstrating that parental monitoring plays a role in the choice of friends with whom adolescents affiliate (Knoester et al 2006), as studies find that high levels of parental monitoring deter affiliation with drug using adolescents (e.g., Bogenschneider et al 1998; Brown et al 1993). Similarly, other research suggests that both the quality and frequency of parental smoking-specific communication was positively related to youths’ selective affiliation with non-smoking friends (Leeuw et al 2008). Consistent with these studies, other research found that parental monitoring had a direct and protective effect against smoking progression among adolescents; in addition, it indirectly affected smoking by inhibiting increases in the acquisition of friends who smoke (Simons-Morton et al 2004).…”
Section: Introductionmentioning
confidence: 78%
“…These interactions are premised upon studies demonstrating that parental monitoring plays a role in the choice of friends with whom adolescents affiliate (Knoester et al 2006), as studies find that high levels of parental monitoring deter affiliation with drug using adolescents (e.g., Bogenschneider et al 1998; Brown et al 1993). Similarly, other research suggests that both the quality and frequency of parental smoking-specific communication was positively related to youths’ selective affiliation with non-smoking friends (Leeuw et al 2008). Consistent with these studies, other research found that parental monitoring had a direct and protective effect against smoking progression among adolescents; in addition, it indirectly affected smoking by inhibiting increases in the acquisition of friends who smoke (Simons-Morton et al 2004).…”
Section: Introductionmentioning
confidence: 78%
“…More frequent communication is associated with higher rates, more positive attitudes towards and lower self-efficacy to refuse cigarette use (de Leeuw et al, 2008(de Leeuw et al, , 2010Harakeh, Scholte, de Vries, & Engels, 2005, Harakeh, Engels, Den Exter Blokland, Scholte, & Vermulst, 2009Harakeh et al, 2010;Hiemstra, Otten, & Engels, 2012;Huver, Engels, & de Vries, 2006; Otten, van der Zwaluw, van der Vorst, & Engels, 2008); higher rates of alcohol use and associated problems (van den Eijnden, van de Mheen, Vet, & Vermulst, 2011;Koning et al, 2013;Spijkerman, van den Eijnden, & Huiberts, 2008;van der Vorst et al, 2005van der Vorst et al, , 2010; and higher rates of cannabis use initiation (Nonnemaker et al, 2012). It is unclear as to the direction of this relationship: parents' frequent communication may be ignored and adolescents start using substances; or parents communicate more frequently when they believe their adolescents are using substances.…”
Section: Frequency Vs Qualitymentioning
confidence: 99%
“…The authors have suggested that the latter may be the case but longitudinal studies are required to examine the direction of the relationship (Harakeh et al, 2005(Harakeh et al, , 2009(Harakeh et al, , 2010Huver et al, 2006;van der Vorst et al, 2005). High quality communication, conversely, is associated with lower rates of smoking, more negative attitudes and higher self-efficacy to refuse cigarette use (de Leeuw et al, 2008;Harakeh et al, 2005Harakeh et al, , 2010Otten et al, 2008;Ringlever, Otten, de Leeuw, & Engels, 2011;; lower rates of alcohol use and higher self-efficacy to refuse (van den Eijnden et al, 2011;Koning et al, 2013;Mares, Lichtwarck-Aschoff, & Engels, 2013;Spijkerman et al, 2008). While Koning et al (2014) found no association between quality of communication and alcohol use, they still promote the use high quality conversations.…”
Section: Frequency Vs Qualitymentioning
confidence: 99%
“…In this procedure all adolescents were collapsed into one group. Standard errors of the parameter estimates were corrected for dependency, resulting in unbiased estimates (see e.g., [11]). No model fit indices were obtained as we tested a saturated path model.…”
Section: J Statistical Analysesmentioning
confidence: 99%